Does Remuneration Affect the Discipline and the Selection of Politicians? Evidence from Pay Harmonization in the European Parliament - Thomas Braendle (University of Basel, Center of Business and Economics (WWZ), 2013)
We study the harmonization of the base remuneration for the Members of the European Parliament (MEPs) who were previously paid like national parliamentarians implying large differences between the delegations from the 27 member countries. Based on detailed information on individual MEPs between 2004 and 2011, we find that the reform, which comes with an exceptional increase of, on average, 200 percent per national delegation, has a positive incentive effect on in-office effort as approximated by engagement in speeches, written declarations and drafted reports. However, a higher remuneration increases absence. With respect to political selection, we find that a higher remuneration increases re-election rates. The composition of the pool of MEPs in terms of (ex-ante) quality approximated with formal education, previous political experience and occupational background is, however, unaffected. If we restrict our attention to freshmen, we find that a higher remuneration is related to a lower fraction of MEPs with previous political experience at the highest national level.
Keywords: D72; D73; 330; Politicas selection; remuneration of politicians; electoral system; European Parliament; Abgeordnete; Politikfinanzierung; Reform; Wahlsystem; EU-Staaten